PENGEMBANGAN MATERI PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN SELF EFFICACY SISWA KELAS X MIA 1 MAN 2 MODEL PEKANBARU TAHUN AJARAN 2015/2016 - Rahayu Putri Anisa; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to develop the use of social media to improve self efficacy materials class X SLTA/MA equel, and description of its feasibility in terms of aspects of clarity, systematics, image support, freshness, completeness of the material, and video or games support . This research using methods of research and development ( R & D ). Data analysis techniques using data validity. The source of the data obtained from the supervisor 1 and 2, 3 teachers guidance and counseling MAN 2 MODEL Pekanbaru, as well as 27 students of class X MIA 1 MAN 2 Model Pekanbaru. This material is tested to the student with the allocation of a 3-hour lessons ( 3 x 45 ' ). This material consists of a sense of self-efficacy, the sources of self-efficacy, understanding social media, the social media revolution , and the benefits of social media. The results of the development of this material indicates the quality of the material produced in the category